Crustal Structure and Evolution of the Eastern Himalayan Plate Boundary System, Northeast India. Issue 1 (27th January 2018) - Mitra, S.; Priestley, K. F.; Borah, Kajaljyoti; Gaur, V. K.
Abstract: We use data from 24 broadband seismographs located south of the Eastern Himalayan plate boundary system to investigate the crustal structure beneath Northeast India. P wave receiver function analysis reveals felsic continental crust beneath the Brahmaputra Valley, Shillong Plateau and Mikir Hills, and mafic thinned passive margin transitional crust (basement layer) beneath the Bengal Basin. Within the continental crust, the central Shillong Plateau and Mikir Hills have the thinnest crust (30 ± 2 km) with similar velocity structure, suggesting a unified origin and uplift history. North of the plateau and Mikir Hills the crustal thickness increases sharply by 8–10 km and is modeled by ∼30 ∘ north dipping Moho flexure. South of the plateau, across the ∼1 km topographic relief of the Dawki Fault, the crustal thickness increases abruptly by 12–13 km and is modeled by downfaulting of the plateau crust, overlain by 13–14 km thick sedimentary layer/rocks of the Bengal Basin. Farther south, beneath central Bengal Basin, the basement layer is thinner (20–22 km) and has higher V s (∼4.1 km s −1 ) indicating a transitional crystalline crust, overlain by the thickest sedimentary layer/rocks (18–20 km). Our models suggest that the uplift of the Shillong Plateau occurred by thrust faulting on the reactivated Dawki Fault, a continent margin paleorift fault, and subsequent back thrusting on the south dipping Oldham Fault, in response to flexural loading of the Eastern Himalaya. Our estimated Dawki Fault offset combined with timing of surface uplift of the plateau reveals a reasonable match between long‐term uplift and convergence rate across the Dawki Fault with present‐day GPS velocities. Key Points: NE India is underlain by continental crust beneath Brahmaputra Valley and Shillong Plateau and mafic transitional crust beneath Bengal Basin N of the plateau crustal thickness increases by 8–10 km with Moho flexure of 30°, and S downfaulted by 12–13 km across the Dawki Fault Shillong Plateau uplift is mediated by thrust faulting on the reactivated Dawki Fault and back thrusting on the north dipping Oldham Fault